Reduction of threading dislocations in GaN grown on patterned sapphire substrate masked with serpentine channel. (1st November 2021) - Khan, Muhammad Saddique Akbar; Liao, Hui; Yu, Guo; Iqbal, Imran; Lei, Menglai; Lang, Rui; Mi, Zehan; Chen, Huanqing; Zong, Hua; Hu, Xiaodong
Abstract: Gallium nitride (GaN) is a promising semiconductor for the fabrication of a wide range of electronic and optoelectronic devices. For GaN grown on widely used sapphire substrate, bundles of threading dislocations (TDs) are induced by thermal and lattice mismatch. These TDs intersect the surface of GaN and degrade the internal quantum efficiency (IQE) of GaN-based devices. To address this issue, two innovative techniques are proposed for effective filtration of TDs. First, a novel design of serpentine channel pattern sapphire substrate (SCPSS) is applied for effective filtration of TDs at the interface. Transmission electron microscopy (TEM) indicated that SCPSS plays an effective role in the filtration of TDs; however, cathodoluminescence (CL) revealed that many TDs still intersect the surface of GaN. To further optimize the growth of GaN, the temperature was ramped down to the intermediate level and an interlayer (IL) of InGaN was introduced near the window of SCPSS. CL analysis indicated that additional use of InGaN-IL further reduced the TDs. Raman microscopy showed that incorporation of IL lead to drastic reduction in compressive stress. Atomic force microscopy (AFM) confirmed the achievement of excellent surface topography with InGaN-IL. Moreover, it is observed that growth of GaN by SCPSS is better than conventional growth because of improved surface morphology and low TDs. The reduction of TDs by SCPSS and InGaN-IL is an effective approach for the growth of high-quality GaN towards efficient devices. Graphical abstract: Image 1 Highlights: - Reduction of TDs in GaN grown by novel design of pattern sapphire substrate. - Role of interlayer of InGaN in the filtration of threading dislocations. - Blocking and bending of threading dislocations by PSS and interlayer of InGaN. - Effects of interlayer of InGaN on the crystal quality of GaN. - High quality growth of GaN grown on SCPSS and role of InGaN interlayer.